Comparison of optical and inertial tracking of full golf swings - Seaman, A.; McPhee, J. (Procedia Engineering, 2012)
We compare optical tracking with inertial tracking of a golf club for full golf swings. Previous work on tracking golf clubs with inertial measurement units (IMUs) was limited to putting applications [1]. Using a Vicon optical motion capture system and a commercial micro-electromechanical-system (MEMS) IMU, we performed simultaneous optical and inertial measurements of golf swings by one of our varsity golf team members. The IMU and five optical tracking markers were attached to a club shaft just under the grip. The position and orientation data of the grip can be used with a dynamics simulation of the club shaft and head to yield information about the club face launch conditions at the moment of ball impact [2]. Vicon marker position data, and IMU accelerations and rotation rates, were converted into laboratory frame position and orientation data for the grip of the club and compared with one another. The results point to challenges with commercial-grade IMUs that use MEMS for tracking golf swings. Strapdown inertial navigation is very sensitive to errors in the rotation rate and acceleration sensors. Due to the large dynamic ranges involved in a golf swing, and the poor noise, stability, and dynamic range of the MEMS IMUs, high-fidelity tracking of the 6-degree-of freedom grip motion could not be achieved. We suggest that a way to overcome these challenges could be by including magnetometer data with an extended Kalman filter to provide the necessary accuracy in orientation to reconstruct the position of the club accurately in three dimensions.